Parental Attitudes Towards School and Everyday Mathematics and Their Engagement in Children’s Mathematical Activities - Antolin Drešar, Darja (Revija za elementarno izobraževanje, 2025)
Although parental involvement plays a crucial role in children’s mathematical education, few studies examine how their attitudes towards mathematics influence their participation in specific activities. This study investigates the relationship between parental attitudes towards mathematics in school and in everyday contexts and their engagement in these activities. Results from a survey of 245 Slovenian parents reveal that most parents exhibit a neutral attitude towards school mathematics, while they generally hold a positive attitude towards the practical use of mathematics. Parents with less positive attitudes towards school mathematics tend to assist their children more often, whereas a positive attitude towards everyday mathematics is associated with greater parental involvement in daily mathematical activities at home.
Keywords: parental attitudes, mathematics education, parental engagement, school mathematics, everyday mathematics.